(untitled) (Fiep Bulletin - online, 2012)
The fight for judo has an intermittent feature, high intensity, so the athletes develop intense efforts during thetournament, firing, therefore, predominantly glycolytic energy pathway production. In this study the main objective was toinvestigate the correlation between performance in a judo competition with the percentage of blood lactate removal and theSterkowicz’s index. Additionally, we analyzed the correlation between heart rate and lactate concentration, and varying themaccording to time. The peak lactate concentration was also observed. Seven judokas over 18 year old male, weighing between60 kg and 66 kg, were submitted on different days, an lactate analysis with the Accutrend Plus®, for the percentage of lactateremoval in 15 minutes, with collections 1, 3, 5, 10 and 15 minutes after the Sterkowicz’s test, and competition in a simple roundrobinfashion simulating a sports tournament. The comparison between the values was performed using Pearson’s correlationcoefficient and Spearman, in program SPSS 17.0 for Windows®. There was a moderate negative correlation (r=- 0,607, p=0,001) between the classification of athletes in judo tournament and blood lactate removal after the same Sterkowicz’s test. Goodcorrelation (r=0,857, p=0,001) between the Sterkowicz’s index and ranking tournament in judo and a weak correlation (r = 0.136,p = 0.001) between heart rate and blood lactate concentration was found. Therefore, the main conclusion of this study was thatthere is a possibility of removal of blood lactate influence the performance of judo athletes and Sterkowicz’s index presentedhimself as a good parameter to discriminate between athletes. However, additional studies are needed to confirm this finding.